PENGARUH KOMPONEN ALOKASI DANA DESA DAN PRODUK DOMESTIK REGIONAL BRUTO TERHADAP TINGKAT KEMISKINAN KABUPATEN /KOTA DI PROVINSI ACEH - Yusniati Yusniati; Murhaban Murhaban; Muammar Khaddafi (J-MIND (Jurnal Manajemen Indonesia), 2020)
Village Fund Allocation is funds originating from the APBN allocated to villages, used to finance village administration, implementation of village development, community development, and empowerment of village communities, in order to alleviate poverty. The purpose of this study was to analyze the effect of village fund allocation for rural development, village community development, empowerment of rural communities and gross regional domestic product on the poverty level of districts / cities in Aceh Province. This research is quantitative using panel data consisting of cross-sectional data, namely 23 regencies / cities with 3-year time series data. Data analysis method is panel data regression using eviews tools. The results of the study showed that the allocation of village funds for village development and village community development had a negative effect on poverty levels. Whereas the allocation of village funds to empower rural communities and gross regional domestic products does not affect the level of poverty. This indicates that the use of village funds prioritizes village development. Furthermore, the overall results of the study indicate that all independent variables simultaneously have a simultaneous effect on the level of poverty. Village fund allocation should not only focus solely on village development. Because the development of the quality of human resources must also get the same portion as the allocation of village funds for development, so that with the advancement of development will be in line with improving the quality of good human resources. Keyword : Components, village funds, gross regional domestic products, poverty